2018
DOI: 10.1155/2018/1374150
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Carbetocin versus Oxytocin in the Prevention of Postpartum Haemorrhage after Caesarean Section: A Randomized Controlled Trial

Abstract: Purpose To compare the incidence of nausea, vomiting, and arterial hypotension between carbetocin and oxytocin to prevent haemorrhage after caesarean section (CS). Methods A randomized controlled trial in term pregnant women undergoing planned CS. Groups were randomized to carbetocin or oxytocin. Blood pressure (BP), heart rate, presence of nausea/vomitus, and need for vasopressors were evaluated throughout surgery. Preoperative and postoperative haemoglobin and haematocrit levels were compared. Results Fifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 13 publications
1
26
0
3
Order By: Relevance
“…Oxytocin can cause water retention and subsequent hyponatraemia, as the drug has a structural analogy with antidiuretic hormone (ADH; vasopressin), and therefore activates the ADH receptor . Oxytocin can cause nausea and vomiting; vomiting occurred in 15% of women after a 5 IU bolus followed by a 10 IU infusion over 24 h . This adverse effect is dose related, as nausea occurred in 5% vs. 33%, and vomiting in 2.5% vs. 15% of women after 2 IU or 5 IU oxytocin, respectively .…”
Section: Oxytocinmentioning
confidence: 99%
“…Oxytocin can cause water retention and subsequent hyponatraemia, as the drug has a structural analogy with antidiuretic hormone (ADH; vasopressin), and therefore activates the ADH receptor . Oxytocin can cause nausea and vomiting; vomiting occurred in 15% of women after a 5 IU bolus followed by a 10 IU infusion over 24 h . This adverse effect is dose related, as nausea occurred in 5% vs. 33%, and vomiting in 2.5% vs. 15% of women after 2 IU or 5 IU oxytocin, respectively .…”
Section: Oxytocinmentioning
confidence: 99%
“…In this study, the adverse events attached to carbetocin are shown to be worse than adverse events attached to oxytocin. However, in the published literature, carbetocin is found to have a similar adverse events profile to oxytocin [ 6 , 7 ], and so in reality, carbetocin is likely to perform slightly better than suggested in Analysis 2.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the carbetocin trials included in the NMA consist of a small sample population [ 16 ]. Carbetocin is the most effective strategy, and is known to have a favourable adverse event profile, similar to oxytocin [ 6 , 7 ]. However, carbetocin has a much higher unit cost than the other uterotonic drugs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of experimental and clinical data provided substantial evidence for hypotensive action of peripherally and centrally administered OT (16,36,44,45). For instance, Gutkowska et al (16) have shown that repeated subcutaneous injections of OT cause diurnal and nocturnal reductions of blood pressure in spontaneously hypertensive rats (SHR).…”
Section: Introductionmentioning
confidence: 99%